A 1 GSPS VME data acquisition module - Loureiro, C. F. M. (1996)
In the following a new data acquisition architecture is proposed allowing high sampling rates along with a large memory data buffer. The modular design allows up to four 250 MHz, 8-bit acquisition channels to operate in an interleaved way, achieving 1 GSPS. Each channel can acquire continuously up to 3 MBytes of data (or 12 MBytes when interleaved). Since several modules can coexist in an acquisition system, provision was made for several parallel operations, including trigger distribution and download of digital signal processing programs. The module will be used in a dedicated acquisition system for the reflectometry diagnostic on the Asdex-Upgrade tokamak